2018
DOI: 10.1680/jgrim.17.00031
|View full text |Cite
|
Sign up to set email alerts
|

Soil improvement using recycled aggregates from demolition waste

Abstract: Fine-grained soils with an in situ water content above the optimum compaction water content show poor suitability for installation and compaction. This paper presents the findings of an experimental study on the improvement of such soils by adding recycled aggregates from demolition waste. The study covers nine different base soils with a wide range of plasticity and addition rates of up to 50 mass% of recycled aggregates with a grain size 0/4 mm. A comparative analysis of the results from the laboratory study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Different researchers ( Pourkhorshidi et al., 2020 ; Zhang et al., 2019 ; Kerni et al., 2015 ; Jayakody et al., 2019 ; Jayatheja et al., 2021 ) found that processed and selected CDW is an excellent option for improving the geotechnical behavior of soil having lower strength and high compressibility for applying in pavement constructions, backfilling materials and structures with lower load, ensuring the recycling and reuse of CDW ( Rahman et al., 2013 , 2014 ; Arulrajah et al., 2019 ; Henzinger and Heyer, 2018 ). Dobrescu and Calarasu (2020) emphasizes the significance of the soil improvement capability of CDW when mixed with soil.…”
Section: Introductionmentioning
confidence: 99%
“…Different researchers ( Pourkhorshidi et al., 2020 ; Zhang et al., 2019 ; Kerni et al., 2015 ; Jayakody et al., 2019 ; Jayatheja et al., 2021 ) found that processed and selected CDW is an excellent option for improving the geotechnical behavior of soil having lower strength and high compressibility for applying in pavement constructions, backfilling materials and structures with lower load, ensuring the recycling and reuse of CDW ( Rahman et al., 2013 , 2014 ; Arulrajah et al., 2019 ; Henzinger and Heyer, 2018 ). Dobrescu and Calarasu (2020) emphasizes the significance of the soil improvement capability of CDW when mixed with soil.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, highly increased in the maximum dry density associated with increases CC up to 10%, beyond exhibits insignificant increases. Henzinger and Heyer (2018) studied experimentally the effect of adding recycled aggregate that produced from demolition waste to fine-grained soils. The recycled aggregate is added by 50% to clay soils with low, medium, and high plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Construction and demolition (C&D) was recognised as one of the priority sectors in this Circular Economy Package due to the vast amounts of C&D wastes generated across the European Union (over 35% of total waste generation), as well as their high potential for circularity. In fact, there has been increasing evidence that C&D materials can successfully be recycled and reused in a variety of civil engineering applications, such as concrete production [ 1 , 2 ], road and railway infrastructure [ 3 , 4 , 5 , 6 ], ground improvement works [ 7 ], geosynthetic-reinforced structures [ 5 , 8 , 9 , 10 , 11 , 12 ], among others. Taking into account that the construction sector is among the main contributors to the natural resource consumption (accounting for ≈50% of all extracted materials), the incorporation of recycled materials in the construction industry could save massive amounts of natural resources and play a notable role in achieving climate neutrality.…”
Section: Introductionmentioning
confidence: 99%